The effects of non-standard forms of employment on worker health and safety - Quinlan, Michael (Geneva, 2016)
"The past 40 years have witnessed significant changes to work arrangements globally. Overall, the changes have been characterised by less contract duration and job security, more irregular working hours (both in terms of duration and consistency), increased use of third parties (temporary employment agencies), growth of various forms of dependent self-employment (like subcontracting and franchising) and also bogus/informal work arrangements (i.e. arrangements deliberately outside the regulatory framework of labour, social protection and other laws)."